2017
DOI: 10.1080/00480169.2017.1329673
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of ryegrass staggers and heat stress in sheep grazing ryegrass-endophyte associations with diverse alkaloid profiles

Abstract: AIMS: To compare ryegrass pastures infected with endophytes producing diverse alkaloids for their ability to cause ryegrass staggers in grazing lambs; to compare respiration rates and rectal temperatures of these lambs after exposure to heat stress, and to compare liveweight gains during the study period.METHODS: Ryegrass pastures of cultivar Trojan infected with NEA endophytes, branded NEA2 (T-NEA2), endophyte-free Trojan (T-NIL), Samson infected with standard endophyte (S-STD), Samson infected with AR37 endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This is well within the concentrations that are typically observed in the field although concentrations of endophyte-expressed alkaloids is weather dependant. It has been reported that in New Zealand under moist, cool conditions in 2012, the total epoxyjanthitrem concentrations ranged between 18.5 and 26.0 ppm in the January to March period, and in 2013 when it was warmer and drier, they ranged from 27.0 to 50.5 in February and March [32].…”
Section: Insect Bioassaymentioning
confidence: 99%
“…This is well within the concentrations that are typically observed in the field although concentrations of endophyte-expressed alkaloids is weather dependant. It has been reported that in New Zealand under moist, cool conditions in 2012, the total epoxyjanthitrem concentrations ranged between 18.5 and 26.0 ppm in the January to March period, and in 2013 when it was warmer and drier, they ranged from 27.0 to 50.5 in February and March [32].…”
Section: Insect Bioassaymentioning
confidence: 99%
“…Other characterised strains which express ergovaline, such as NEA2, have been commercialised (Stewart et al 2014). While this endophyte brand is a mix of NEA2 and NEA6 it is promoted as expressing only low levels of lolitrem B and ergovaline they have the potential to produce toxic concentrations under adverse environmental conditions and have reached 0.9 μg/g DM of ergovaline in autumn Fletcher et al 2017).…”
Section: Epichloë Genetic Strain Effects On Ergovaline Expressionmentioning
confidence: 99%
“…Some of these characterised Epichloë endophyte strains associated with ryegrass, such as AR5, AR6 and some NEA brand endophytes, that either have been or are commercially available, can produce ergovaline concentrations similar to those found in ryegrass with its standard endophyte and depending on host genetics can reach 1.1 μg/g DM (van Zijll de Jong et al 2008;Logan et al 2015). This can result in heat stress responses similar to that of the standard endophyte (Fletcher et al 2017).…”
Section: Epichloë Genetic Strain Effects On Ergovaline Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…NEA2 produces all three alkaloids but at more moderate levels than the E+ strain. AR1 produces only peramine, while AR37 does not produce any of the three alkaloids found in the E+ strain but rather produces a different set called epoxy-janthitrems (see [52] and references therein). These so-called "novel" strains induce other metabolic changes in the host plants beyond the differences in alkaloid production [53][54][55].…”
Section: Introductionmentioning
confidence: 99%